2006
DOI: 10.1590/s0103-863x2006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Inteligência emocional e desempenho no trabalho: um estudo com MSCEIT, BPR-5 e 16PF

Abstract: O presente trabalho teve como objetivo investigar a validade de uma medida de inteligência emocional correlacionando-a com medidas de inteligência, personalidade e desempenho profissional. Participaram do estudo 119 sujeitos, com idade entre 17 e 64 anos, de ambos os sexos e que trabalham em empresas situadas em municípios do interior do estado de São Paulo. Os instrumentos utilizados foram: Versão em Português do Mayer-Salovey-Caruso-Emotional Intelligence Test (MSCEIT), o Questionário Dezesseis Fatores da Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
(8 reference statements)
0
5
0
17
Order By: Relevance
“…The association between these three constructs was not found in the literature. Despite of that, there is enough research that shows the positive influence of Emotional Intelligence in satisfaction (Franca & Mónico, 2014), self-esteem (Mónico, Santos, & Lima, 2014), and in individual and group performance, and also the negative impact on stress (Lucas & Mónico, 2013) and turnover intention (e.g., Cobero et al, 2006). We found that self-encouragement promotes an increase in the perception of Workplace Spirituality.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The association between these three constructs was not found in the literature. Despite of that, there is enough research that shows the positive influence of Emotional Intelligence in satisfaction (Franca & Mónico, 2014), self-esteem (Mónico, Santos, & Lima, 2014), and in individual and group performance, and also the negative impact on stress (Lucas & Mónico, 2013) and turnover intention (e.g., Cobero et al, 2006). We found that self-encouragement promotes an increase in the perception of Workplace Spirituality.…”
Section: Discussionmentioning
confidence: 60%
“…This idea came from Goleman (1995), who disseminated that Emotional Intelligence would be the most important capability to explain the success at work, leading companies to invest in training and changing their selection practices. People with high Emotional Intelligence would present an effective performance at work, assuming the existence of the construct and its utility, without, however, relying on this one empirical data (Cobero, Primi, & Muniz, 2006;Sousa, Mónico & Castro, 2012). There are few studies relating Emotional Intelligence with Psychological Capital.…”
Section: Objetivo(s)mentioning
confidence: 99%
“…The concept of Emotional Intelligence arises proposed by John D. Mayer and Peter Salovey in 1990 [28], through an article in the magazine "Imagination, Cognition and Personality" [29], and not by Daniel Goleman as often judged. It is observable a stimulating body of research in EI, but with a still lack of onceptual consensus which led to a different measuring instruments proliferation [30].…”
Section: Emotional Intelligencementioning
confidence: 99%
“…The predictive value of Emotional Intelligence is important for several areas, such as life satisfaction [34,35], research and clinical application [36], school environment and academic success [14,15] and organizational context, where EI is able to predict the good performance and work success [22][23][24][25][26][27][28][29][30][31][32][33][34], as well as contribute to a better working environment [37]. In organizational reality is patent the magnanimity of emotion by the people that integrate it.…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Nesse instrumento cada uma das quatro habilidades básicas é avaliada por duas provas primárias, de modo que o teste todo é composto por oito tarefas dispostas em 141 itens. Vários estudos atestaram sua validade fatorial, embora com alguma discrepância quanto o número de fatores encontrados (Bueno, 2008;Cobêro, 2004;Dantas, 2004;Jesus Jr., 2004;Mayer, Caruso & Salovey, 1999;Mayer, Salovey, Caruso & Sitarenios, 2003;Palmer, Gignac, Manocha & Stough, 2005;Zeidner, Matthews & Roberts, 2001), assim como sua convergência com medidas tradicionais de inteligência (Cobêro, Primi & Muniz, 2006;Mayer e cols., 1999;Pelletteri, 1999) e independência de traços de personalidade (Bastian, Burns & Nettelbeck, 2005;.…”
Section: Introductionunclassified